Variable Interest Entity Structure as a Form of Investment Undertaken by Chinese Companies on Foreign Stock Exchanges - Sylwia Cieślik (Finanse i Prawo Finansowe, 2021)
The aim of the article: The purpose of this article is to discuss theoretical issues concerning the nature of the Variable Interest Entity (VIE) structure and to analyze the scale and functioning of companies using this structure to issue securities on foreign exchanges. The main research hypothesis was that the VIE structure is widely used by Chinese companies to issue securities on international stock exchanges.